A spleen tyrosine kinase inhibitor attenuates the proliferation and migration of vascular smooth muscle cells. Issue 1 (December 2017) - Seo, Hyang-Hee; Kim, Sang; Lee, Chang; Lim, Kyu; Lee, Jiyun; Choi, Eunhyun; Lim, Soyeon; Lee, Seahyoung; Hwang, Ki-Chul
Abstract Background Pathologic vascular smooth muscle cell (VSMC) proliferation and migration after vascular injury promotes the development of occlusive vascular disease. Therefore, an effective chemical agent to suppress aberrant proliferation and migration of VSMCs can be a potential therapeutic modality for occlusive vascular disease such as atherosclerosis and restenosis. To find an anti-proliferative chemical agent for VSMCs, we screened an in-house small molecule library, and the selected small molecule was further validated for its anti-proliferative effect on VSMCs using multiple approaches, such as cell proliferation assays, wound healing assays, transwell migration assays, and ex vivo aortic ring assay. Results Among 43 initially screened small molecule inhibitors of kinases that have no known anti-proliferative effect on VSMCs, a spleen tyrosine kinase (Syk) inhibitor (BAY61-3606) showed significant anti-proliferative effect on VSMCs. Further experiments indicated that BAY61 attenuated the VSMC proliferation in both concentration- and time-dependent manner, and it also significantly suppressed the migration of VSMCs as assessed by both wound healing assays and transwell assays. Additionally, BAY61 suppressed the sprouting of VSMCs from endothelium-removed aortic rings. Conclusion The present study identified a Syk kinase inhibitor as a potent VSMC proliferation and migration inhibitor and warrants further studies to elucidate its underlying molecular mechanisms, such as its primary target, and to validate its in vivo efficacy as a therapeutic agent for restenosis and atherosclerosis.